2018
DOI: 10.1177/1462474518782470
|View full text |Cite
|
Sign up to set email alerts
|

Nongovernmental organizations and postprison life: Examining the role of religion

Abstract: This article examines the relevance of religion for nongovernmental organizations that work with formerly incarcerated people. Despite the increased visibility of religious nongovernmental organizations working with criminalized people, research on the nongovernmental sector and criminal justice still largely focuses on secular organizations. This article argues for the conceptual importance of religion and its role shaping work in this sector, and draws from the sociology of religion to theorize the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…This also applies to faith communities; Beckford () makes the point that members of ethno‐religious minorities are among the groups in society disproportionately under‐represented in formal volunteering. Both chaplaincies in this study received practical and financial help from local faith groups, but both suggested that there was scope for these groups to do more to support people leaving prison to participate in community life; faith communities do not always welcome people leaving prison (Kaufman ). There is more to be understood about the ways that religion matters in the penal voluntary sector.…”
Section: Discussion: Moving Between Worldsmentioning
confidence: 99%
See 2 more Smart Citations
“…This also applies to faith communities; Beckford () makes the point that members of ethno‐religious minorities are among the groups in society disproportionately under‐represented in formal volunteering. Both chaplaincies in this study received practical and financial help from local faith groups, but both suggested that there was scope for these groups to do more to support people leaving prison to participate in community life; faith communities do not always welcome people leaving prison (Kaufman ). There is more to be understood about the ways that religion matters in the penal voluntary sector.…”
Section: Discussion: Moving Between Worldsmentioning
confidence: 99%
“…This is an approach that values inclusion, forbids overt evangelism and responds to spiritual needs only if those are identified by service users. In similar vein, drawing on research conducted in the US, Kaufman () characterises non‐governmental organisations working with people leaving prison according to the organisation's relationship with religion. In this framework, community chaplaincy is ‘religiously inspired’ as it is ‘guided by loosely and not dogmatically understood religious principles’ (p. 8).…”
Section: The Faith‐based Voluntary Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Recent suggestions have been made that theology may have more to offer on matters related to the subjects of punishment, corrections, and rehabilitation than has often been acknowledged in the scholarly literature (Murphy 2003;Garvey 2003;Kaufman 2018). This includes not only the questions that particular theological frameworks and analytic tools bring for addressing these matters in the era of mass incarceration, and even the underlying theological foundations that gave rise to the contemporary situation, but also new forms of recourse and plausibility structures that may emerge as theological conceptualities are deployed, especially for explanatory research knowledge accounting for various experiential phenomena that includes both practices as well as conceptual structures that give rise to these various dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Voluntary organisations are heterogeneous, but are often registered charities. Differences include: functions; participants; income ranges; funding sources; size; aims; volunteer/paid staff/ex‐offender proportions; relationship(s) with statutory agencies; faith/secular basis (Kaufman ; Tomczak ).…”
mentioning
confidence: 99%